VENTRICULOPERITONEAL SHUNT BLOCKAGE - Hussain, Mubarak; Raja, Riaz A; Shaikh, Aleem -ud-Din; Ali, Mohammad Hamid (Journal of Ayub Medical College Abbottabad, 2012)
Background: Hydrocephalus is the abnormal accumulation of cerebrospinal fluid within the ventricles and subarachnoid spaces, resulting in increased intracranial pressure. The treatment of choice is placement of ventriculoperitoneal shunt. Ventriculoperitoneal shunt blockage is not an uncommon complication. Objective of the study was to find out the frequency, causes and site of ventriculoperitoneal blockage and to compare it with other studies. Methods: This case series study was conducted at Department of Neurosurgery Liaquat University Hospital, Jamshoro, from April 2008 to March 2012. The records of 53 patients between 40 days to 45 years age presenting with blocked ventriculoperitoneal shunt were included. All the patients underwent thorough clinical examination and radiological investigations, and shunt revision done. The retrieved data was collected on proforma. Frequencies and percentages were calculated for categorical data. Results: Out of 53 patients 28 were males, 25 patients were females. Age of patients ranged from 40 days to 45 years. Time interval between the ventriculo-peritoneal shunt placement and blockage of shunt ranged from 2 weeks to 9 years. Out of 53 patients, 32 (69.37%) patients had obstruction at distal catheter, whereas 21 (39.62%) patients had ventricular catheter blockage. Conclusion: Ventriculo-peritoneal shunt blockage is one of the most common complications of shunt placement procedure. In this study most of the patients (69.37%) had distal catheter obstruction. Majority (35.84%) of the patients presented with shunt obstruction within one year of shunt placement. Shunt obstruction is common in children less than 3 years age. Keywords: VP shunt, obstruction of shunt, revision